Investigation of Causal Effects of Protein Biomarkers on Cardiovascular Disease in Persons With HIV. (29th December 2022) - Reilly, Cavan S; Borges, Álvaro H; Baker, Jason V; Safo, Sandra E; Sharma, Shweta; Polizzotto, Mark N; Pankow, James S; Hu, Xiaojun; Sherman, Brad T; Babiker, Abdel G; Lundgren, Jens D; Lane, H Clifford
Abstract: Background: There is an incompletely understood increased risk for cardiovascular disease (CVD) among people with HIV (PWH). We investigated if a collection of biomarkers were associated with CVD among PWH. Mendelian randomization (MR) was used to identify potentially causal associations. Methods: Data from follow-up in 4 large trials among PWH were used to identify 131 incident CVD cases and they were matched to 259 participants without incident CVD (controls). Tests of associations between 460 baseline protein levels and case status were conducted. Results: Univariate analysis found CLEC6A, HGF, IL-6, IL-10RB, and IGFBP7 as being associated with case status and a multivariate model identified 3 of these: CLEC6A (odds ratio [OR] = 1.48, P = .037), HGF (OR = 1.83, P = .012), and IL-6 (OR = 1.45, P = .016). MR methods identified 5 significantly associated proteins: AXL, CHI3L1, GAS6, IL-6RA, and SCGB3A2. Conclusions: These results implicate inflammatory and fibrotic processes as contributing to CVD. While some of these biomarkers are well established in the general population and in PWH (IL-6 and its receptor), some are novel to PWH (HGF, AXL, and GAS6) and some are novel overall (CLEC6A). Further investigation into the uniqueness of these biomarkers in PWH and the role of these biomarkers as targets among PWH is warranted. Abstract : Using a collection of protein panels, associations between baseline protein levels and incident CVD were examined. Associations were detected between several proteins and incident CVD and a causal role for some of these associations was found using mendelian randomization.